2016
DOI: 10.1149/07204.0249ecst
|View full text |Cite
|
Sign up to set email alerts
|

Crystallinity Evaluation of Low Temperature Polycrystalline Silicon Thin Film Using UV/Visible Raman Spectroscopy

Abstract: Low temperature poly-Si (LTPS) is one of the most important high mobility channel materials for thin film transistors (TFTs). However, the improvement of the LTPS TFT performance is limited by the grain size and crystallinity variation. Thus, advanced nondestructive and high-resolution evaluation techniques are needed for LTPS thin film to monitor its crystallinity and grain size distribution. We evaluated the crystallinity of LTPS thin film during the fabrication process with various conditions using UV/visib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…The excitation source was a UV (λ = 355 nm) laser with a penetration depth in the bulk Si of approximately 5 nm under the backscattering geometry. 25,26) In addition, we confirmed that the absorption coefficients do not change with the annealing conditions by ellipsometry. Therefore, it is possible to measure Raman spectra from poly-Si without disturbance from the Si substrate.…”
Section: Experimental Methodssupporting
confidence: 73%
“…The excitation source was a UV (λ = 355 nm) laser with a penetration depth in the bulk Si of approximately 5 nm under the backscattering geometry. 25,26) In addition, we confirmed that the absorption coefficients do not change with the annealing conditions by ellipsometry. Therefore, it is possible to measure Raman spectra from poly-Si without disturbance from the Si substrate.…”
Section: Experimental Methodssupporting
confidence: 73%
“…The numerical aperture (NA) of the lens was 0.5 for the refractive index of air at 1.0. The excitation source was a UV ( = 355 nm) laser with a penetration depth in the bulk Si of approximately 5 nm under the backscattering geometry (15,16). In addition, we confirmed that the absorption coefficients of poly-Si thin films did not change with the annealing conditions by spectroscopic ellipsometry.…”
Section: Figure 1 Schematics Of Poly-si Thin Film Formation Processessupporting
confidence: 60%
“…At present stage, oxide semiconductors are widely used in TFT (Thin Film Transistors) as a channel material (16)(17)(18)(19)(20)(21)(22). Another candidate material is poly-Si (23)(24). In order to demonstrate comparable properties to these materials, the film has to operate in enhancement mode when used as channel.…”
Section: Introductionmentioning
confidence: 99%